Bullying in Brazilian schools: results from the National School-based Health Survey (PeNSE), 2009 - Malta,Deborah Carvalho (2010)
The aim of this study is to identify and describe the occurrence of bullying among students in the 9th year (8th grade) from public and private schools from 26 Brazilian state capitals and the Federal District. It is a cross-sectional study involving 60,973 students and 1,453 public and private schools. Data analysis indicates that 5.4% (IC95%: 5.1%-5.7%) of students reported having suffered bullying almost always or always in the last 30 days, 25.4% (IC95%: 24.8%-26.0%) were rarely or sometimes the victim of bullying and 69.2% (IC95%: 68.5%-69.8%) of students felt no humiliation or provocation at school. The capital with higher frequency of bullying was Belo Horizonte (6.9%; IC95%: 5,9%-7,9%), Minas Gerais, and the lowest was Palmas (3.5%; IC95%: 2.6%-4.5%), Tocantins. Boys reported more bullying (6,0%; IC95%: 5.5%-6.5%) compared with girls (4,8%; IC95%: 4.4%-5.3%). There was no difference between public schools 5.5% (IC95%: 5.1%-5.8%) and private (5.2%) (IC95%: 4.6%-5.8%), except in Aracaju, Sergipe, that show more bullying in private schools. The findings indicate an urgent need for intersectoral action from educational policies and practices that enforce the reduction and prevention of the occurrence of bullying in schools in Brazil.